Identifikasi Perubahan Tutupan Lahan Daerah Aliran Sungai (DAS) Sumpur Menggunakan Citra Landsat 8 Oli Tahun 2014-2024 - Marantika, Dewi; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
The tendency of people to live in river basins will trigger the growth of settlements and human activities that require more land. This causes an increase in land requirements in river basins. As a result, there is a change in land use around the river basin, which was originally a vegetated forest area to become non-vegetated, resulting in a decrease in the carrying capacity of the watershed. This research aims to determine how much land cover has changed in the Sumpur watershed over the last 10 years (2014-2024). This type of research is quantitative with a spatial descriptive approach. The method for making land cover maps for the Sumpur watershed is supervised classification. Meanwhile, the method used to calculate the area of land cover change is through the calculate geometry tool. The results of the research show that land cover changes occurred in the Sumpur watershed from 2014 to 2024. The most extensive increase in land change occurred on built-up land and moors/fields. Meanwhile, other types of land cover such as forests, rice fields and mixed gardens tend to experience a decline. Land previously used for agriculture or forests was converted into built-up land for various development purposes.